1996
DOI: 10.1128/mcb.16.4.1527
|View full text |Cite
|
Sign up to set email alerts
|

Cig2, a B-Type Cyclin, Promotes the Onset of S in Schizosaccharomyces pombe

Abstract: Cdc2, a catalytic subunit of cyclin-dependent kinases, is required for both the G 1 -to-S and G 2 -to-M transitions in the fission yeast Schizosaccharomyces pombe. Cdc13, a B-type cyclin, is required for the M-phase induction function of Cdc2. Two additional B-type cyclins, Cig1 and Cig2, have been identified in S. pombe, but none of the B-type cyclins are individually required for the onset of S. We report that Cdc13 is important for DNA replication in a strain lacking Cig2. Unlike ⌬cdc13 cells, double-mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 38 publications
7
100
0
2
Order By: Relevance
“…Our new findings raise the question of whether the Rum1 effect is due to inhibition of Cdc2-Cdc13 or Cdc2-Cig2. We favor the latter possibility, largely because Cdc2-Cig2 is more active than Cdc2-Cdc13 during S phase, at least when both complexes are assayed as histone H1 kinases in vitro (Mondesert et al, 1996). We propose that there is a rather brief window during S phase in which reduction of Cdc2 kinase activity will rescue cdc18-K9, and it is during this window that Cdc2-Cig2 kinase is most active.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our new findings raise the question of whether the Rum1 effect is due to inhibition of Cdc2-Cdc13 or Cdc2-Cig2. We favor the latter possibility, largely because Cdc2-Cig2 is more active than Cdc2-Cdc13 during S phase, at least when both complexes are assayed as histone H1 kinases in vitro (Mondesert et al, 1996). We propose that there is a rather brief window during S phase in which reduction of Cdc2 kinase activity will rescue cdc18-K9, and it is during this window that Cdc2-Cig2 kinase is most active.…”
Section: Discussionmentioning
confidence: 95%
“…However, previous studies indicated that Cdc2-Cig2 kinase is exclusively involved in promoting the onset of S phase from G 1 phase (Fisher and Nurse, 1996;Martin-Castellanos et al, 1996;Mondesert et al, 1996). Therefore, the association involving Cdc18 and Cig2 was inconsistent with the hypothesis that phosphorylation of Cdc18 catalyzed by Cdc2 has a purely inhibitory role.…”
Section: Role Of Cig2 In the Negative Regulation Of Cdc18mentioning
confidence: 93%
See 1 more Smart Citation
“…It was demonstrated that the Cig2 cyclin was a major partner of the Cdc2 kinase in the G 1 /S-phase in fission yeast (Fisher and Nurse, 1996;Martín-Castellanos et al, 1996;Mondesert et al, 1996). Cells harboring the deleted cig2 allele are viable but exhibit a delay in progression through G 1 to the S-phase in some situations, e.g., small cells generated by the wee mutations or nitrogen starvation.…”
Section: The Ste9 ؉ Gene Is Essential For G 1 Arrest Upon Starvationmentioning
confidence: 99%
“…In animal cells this phosphorylation is carried out by Wee1 and Myt1 kinases, with the latter enzyme also phosphorylating the preceding threonine residue (7,(12)(13)(14)(15)(16)(17). Dephosphorylation of these residues and consequent activation of Cdc2 is largely carried out by Cdc25 dual specificity phosphatase (18 -24), although other phosphatases may weakly contribute to the activation of Cdc2-cyclin B (25,26).…”
mentioning
confidence: 99%